Road Traffic Injuries: Children and their Parental Perspectives towards Emergency Medical - Kharel, Krishna; Giri, Surendra; Aryal, Sulocahana (HPE Forum, 2026)
Road traffic injuries are a major global public health concern and a leading cause of death and disability among children and adolescents, particularly those aged five to fourteen years who are more vulnerable due to increased exposure to road hazards and limited understanding of traffic safety. This qualitative case study aimed to explore the experiences and perceptions of school children injured in road traffic accidents and to examine their health-seeking behaviors following the incidents. The study was conducted in Butwal Sub-Metropolitan City, Rupandehi District, Nepal, focusing on cases reported during the fiscal year 2078/2079. Participants included five injured school children and their parents. Data were collected through in-depth interviews with children, semi-structured interviews with parents and the participants’ hospital treatment documents and they were analyzed thematically using Flyvbjerg (2011) seven-step framework. Findings exposed critical gaps in the quality of emergency care in government hospitals, such as inadequate staff training and lack of child friendly environments. In contrast, private hospitals were perceived as offering better care due to superior facilities and resource availability, despite higher costs. The study underlines the crucial need to strengthen emergency healthcare services, improve pre-hospital care, ensure equitable access to treatment and foster public private collaboration.